Preparation and characterization of nanosilica from rice husk ash by chemical treatment combined with calcination - Anh Tuan, Le Nghiem; Kim Dung, Lai Thi; Thanh Ha, Le Doan; Hien, Nguyen Quoc; Phu, Dang Van; Du, Bui Duy (Vietnam Journal of Chemistry, 2017)
This work presented the results of the study on synthesis and characterization of nanosilica from rice husk ash (RHA). Nanosilica was obtained by calcination of HCl treated RHA at 700 oC for 2 h. X-ray diffraction (XRD) pattern showed only one peak at 2q ~22o confirming the amorphous structure of nanosilica. The chemical composition assessed by energy dispersive X-ray spectroscopy (EDX) showed that the obtained nanosilica was of high purity. TEM image measured by transmission electron microscopy (TEM) revealed that the obtained nanosilica was in spherical morphology with the average diameter of about 45.5±7.2 nm. The particle size distribution of nanosilica determined by dynamic laser scattering (DLS) was of Gaussian mode. The FTIR spectrum indicated the presence of silanol and siloxane groups in nanosilica. Thus, the synthesized nanosilica can be used for application in different fields. Keywords. Rice husk ash, nanosilica, amorphous.